Perspectivas teológicas para o combate à idolatria - Ribeiro, Cláudio de Oliveira (Revista Eclesiástica Brasileira, 2005)
A partir da aproximação teológica de Paul Tillich, o A. aponta para algumas perspectivas que podem enriquecer o atual panorama teológico-pastoral latino-americano e, conseqüentemente prevenir o risco de idolatrias. Entre as perspectivas estão a ênfase no equilíbrio entre a dimensão intra-histórica e a transcendente da categoria Reino de Deus (questionando tanto setores da Teologia da Libertação como da Teologia da Prosperidade), o diálogo inter-religioso instado a refletir sobre o lugar da dimensão salvífica, bem como a valorização da tradição bíblico-sapiencial junto à do Êxodo, para fazer frente à degradação sócio-religiosa latino-americana. Abstract: Having as background Paul Tillich’s theological approach, the Author points to some perspectives that could enrich the present Latin American theological-pastoral panorama and consequently reduce the risk of idolatries. Among these perspectives, he focuses in particular on the emphasis given to the balance between the inter-historical and transcendental dimensions of the category Kingdom of God (challenging some sectors of the Theology of Liberation as well as of the Theology of Prosperity); on the inter-religious dialogue from which is demanded a reflection about the place of the salvific dimension; and on the valorization of the biblical-sapiential tradition vis a vis the Exodus’ tradition, all useful instruments in the struggle against the Latin American social-religious degradation.